The Agriculture and Society in the Yiluo River Basin: Archaeobotanical Evidence From the Suyang Site - Yang, Fan; Duan, Qimeng; Cheng, Baozeng; Ren, Guang; Jia, Yin; Jin, Guiyun (Frontiers in Earth Science, 2022)
The Yiluo River basin is located in the central plains of China, an area commonly known as the center of origin of ancient Chinese civilization. Agriculture lays the foundation for social and economic development and triggers societal change. However, relatively few archaeobotanical studies have been conducted in the Yiluo River basin, and the paucity of data has hindered our understanding of the relationship between agriculture and society. Therefore, the archaeobotanical analysis at the Suyang site in the middle reach of the Luo River provides an opportunity to understand the problem. Our analytical results of carbonized plant remains and phytolith, coupled with radiocarbon dating, showed that millet was the main crop in the late Yangshao culture(5500-5000BP), followed by rice. However, rice cultivation in the area expanded during the Longshan culture(5000-4000BP), and its importance as a crop possibly exceeded millet at Suyang. From late Yangshao to Longshan, rice was cultivated in wet fields by utilizing the Luo River floodplain on a large scale. The proportion of rice at Suyang is the highest among contemporary sites in the Central Plains. It may be related to many reasons such as suitable environmental and geomorphological conditions, advanced water resource management, the influence of Qujialing culture, and population growth. In the late Yangshao culture, crop processing seemed to have been concentrated in communal areas. However, during the Longshan culture, different steps of crop processing were scattered throughout the site. This change is hypothesized as a change in the family structure and economic production. After the Yangshao period, the nuclear family became the fundamental unit for social, cultural, and economic production in the central plains.